Kibble-Zurek exponent and chiral transition of the period-4 phase of Rydberg chains - Natalia Chepiga (Nature Portfolio, 2021)
Phase transition occurring in quantum material is an intriguing phenomenon. Here, the authors discuss the commensurate-incommensurate phase transition out of the period-4 phase on a chain of Rydberg atoms and emphasize the emergence of a chiral transition.